2005
DOI: 10.1001/archpsyc.62.5.505
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Multisite Randomized Trial of Supported Employment Interventions for Individuals With Severe Mental Illness

Abstract: The SE models tailored by integrating clinical and vocational services were more effective than services as usual or unenhanced services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
179
1
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 246 publications
(194 citation statements)
references
References 31 publications
8
179
1
6
Order By: Relevance
“…As a secondary outcome, we assessed the wages earned from competitive employment. The data for competitive employment corresponded to outcomes derived from integrated paid work with at least minimum wage, and not reserved for people with disabilities [21]. The data for any employment corresponded to outcomes derived from any paid work, including sheltered workshops or transitional employment with wages.…”
Section: Outcomes Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…As a secondary outcome, we assessed the wages earned from competitive employment. The data for competitive employment corresponded to outcomes derived from integrated paid work with at least minimum wage, and not reserved for people with disabilities [21]. The data for any employment corresponded to outcomes derived from any paid work, including sheltered workshops or transitional employment with wages.…”
Section: Outcomes Measuresmentioning
confidence: 99%
“…of competitive employment [21]. When we could not establish which type of employment outcome was obtained, we used a conservative approach and coded the outcome as any job.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…The IPS model of SE [12][13][14][15][16] emphasizes rapid job placement, competitive jobs, ongoing support without a time limit, client choice of jobs, integration of vocational support and clinical care, and openness to all who want to work [17]. Clinical trials have shown IPS to be associated with higher CE rates, shorter time to entering CE, greater numbers of hours worked per week, and more weeks worked per year among individuals diagnosed with SMI [13,[16][17][18][19][20][21][22][23][24][25][26] and, most recently, among veterans with posttraumatic stress disorder (PTSD) [27].…”
Section: Supported Employmentmentioning
confidence: 99%
“…Analysis of data from a national household survey revealed that more than three-quarters (77%) of the general working-age population are employed in a given year, while less than one-fifth (17%) of those with severe mental health conditions are working [1]. Supported employment, an evidence-based practice (EBP) for enhancing employment outcomes among people with severe mental illness, is available [2][3]. However, many outpatients have co-occurring physical illnesses, chronic medical conditions, and disabilities that also impair vocational performance and may affect their ability to benefit from supported employment services.…”
Section: Introductionmentioning
confidence: 99%